RAGAM PEMBACAAN HADIS Memahami Hadis Melalui Tatapan Postradisionalisme - Firdausy, Hilmy (IAIN Pekalongan, 2016)
As one of the two influental doctrinal texts, Hadith have a central role in the legalization of understanding verses of the al-Qur’an by referring directly to the practice of the Prophet. In the midst of ideo-political constellation in the Islamic world, until now activities to understanding Hadith is much influenced by the way is relativized balance read the dialogue between text and reader; both in the case of the text that was sunk by the existence of the reader, or the reader is immersed in the text and the memory of his past. From some of the existing models, there are at least three reading modes can be considered superior; Salafi-Fundamentalism, Salafi-Orientalism and Reformist-Marxism. This paper will do a critique of reason on how to read these as well as build an applied